Association of white matter hyperintensities with lipoprotein (a) levels: insights from a cohort study - Alotaibi, Fawaz F.; Mohamed, Gamal; Bakry, Sawsan S.; Alqahtani, Mohammed; BinAmir, Hussain; AlKawi, Ammar; Alreshaid, Abdulrahman A.; AlZawahmaha, Mohamed; Alhazzani, Adel; Shuaib, Ashfaq; Al-Ajlan, Fahad S. (Frontiers in Neurology, 2024)
BackgroundLittle is known about the relationship between lipoprotein (a) [Lp(a)] and cerebral white matter hyperintensities (WMH). The aim of the study was to examine if elevated Lp(a) levels are associated with higher burden of WMH.MethodsWe retrospectively investigated associations between Lp(a) and the burden of WMH among patients with confirmed diagnosis of acute ischemic stroke or transient ischemic attacks. WMH burden was assessed using 3-Tesla brain MRI and graded according to the Fazekas score. Multivariable models were generated to determine the contribution of Lp(a) to the presence and extent of WMH.ResultsOne hundred and fifty-three patients were included (mean age, 45.9 years; 35.9% women). When the study population was stratified by Lp(a) level into three categories, low (<75 nmol/L), moderate (75 to <125 nmol/L), and high (≥125 nmol/L), the distribution of the three groups was 60.8, 15.0 and 24.2%, respectively. High Lp(a) Level was associated with higher burden of both periventricular WMH and deep WMH compared to the lower level (odds ratio [OR], 4.4; 95% confidence interval [CI], 1.60–12.07; p = 0.004; and OR, 5.6; CI, 1.69–14.7; p = 0.001, respectively).ConclusionWe show in this cohort of patients that a higher burden of WMH was observed in patients with higher level of Lp(a). Further studies are needed to confirm this observation and assess whether lowering Lp(a) level may be a potential therapeutic target for mitigating the development of WMH.